Touchless interaction in surgery - O'Hara, Kenton; Gonzalez, Gerardo; Sellen, Abigail; Penney, Graeme; Varnavas, Andreas; Mentis, Helena; Criminisi, Antonio; Corish, Robert; Rouncefield, Mark; Dastur, Neville; Carrell, Tom (Communications of The ACM, 2014)
Touchless interaction with medical images lets surgeons maintain sterility during surgical procedures.